2019
DOI: 10.1002/ccd.28226
|View full text |Cite
|
Sign up to set email alerts
|

VitaFlow™ transcatheter valve system in the treatment of severe aortic stenosis: One‐year results of a multicenter study

Abstract: Objective: This study reports the 1-year clinical outcomes of the VitaFlow™ transcatheter aortic valve system in the treatment of severe aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
(28 reference statements)
4
41
0
Order By: Relevance
“…Venus-A is the first THV that has been certified for clinical use in China, which is designed with a long selfexpandable nitinol stent 10) . In our cohort, 19.0% of the patients who received Venus-A prosthesis required a new PPI, in accordance with the patients with an implanted CoreValve or VitaFlow 11) prosthesis of which support frame is similar to Venus-A. 10) It has been well demonstrated that the incidence of PPI was higher in TAVI patients using Medtronic CoreValve than those using Edwards SAPIEN.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Venus-A is the first THV that has been certified for clinical use in China, which is designed with a long selfexpandable nitinol stent 10) . In our cohort, 19.0% of the patients who received Venus-A prosthesis required a new PPI, in accordance with the patients with an implanted CoreValve or VitaFlow 11) prosthesis of which support frame is similar to Venus-A. 10) It has been well demonstrated that the incidence of PPI was higher in TAVI patients using Medtronic CoreValve than those using Edwards SAPIEN.…”
Section: Discussionsupporting
confidence: 77%
“…We observed that the rate of PPI was significantly lower in patients who were treated with J-Valve (4.3%) than in those who were re-ported with Edwards SAPIEN 22,23) or Medtronic Core-Valve 24) or other THVs. 11,25,26) We speculated the reasons for the lower rate of PPI in patients using J-Valve as follows: (1) The connecting sutures between valve body and positioning element 7) can prevent deep positioning of the prosthesis within left ventricular outflow tract during THV In TAVI procedure, this is an effective way to avoid the complete AV block that may directly result from the compression caused by THV devices, 27) leading to a lower incidence of third-degree AV block. (2) The lesser radial force of support frame could reduce excessive compression on calcified aortic valve/annular, which may be FRAME DESIGN OF PROSTHESIS AFFECT TAVI RESULTS another contributing factor to this advantage of J-Valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three self‐expanding transcatheter heart valves (THV), CoreValve, Venus A‐valve, 14 VitaFlow valve, 15 as well as Lotus valve were utilized during the study period in our center. A 29/31 mm CoreValve, 29/32 mm Venus A‐valve, 27 mm VitaFlow valve and 25/27 mm Lotus valve were regarded as the large THV sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Three self-expanding transcatheter heart valves (THV), CoreValve, Venus A-valve, 14 VitaFlow valve, 15…”
Section: Tavr Proceduresmentioning
confidence: 99%